What is the relationship between body mass index and reaction speed in PPLOP boxing athletes in Central Java? - Islam, Syahrizal; Husein, Muhamad; Abadi, Akabar Kusuma; Pratama, Okky Putra Alwin; Nubatonis, Jefrio Demitrimus; Kristiono, Aljawahir Agus; Dewi, Indah Sari; Wijaya, Muhammad Budi; Salacup, Vince Louisse D. (Tanjungpura Journal of Coaching Research, 2024)
Background and Study Aim. Boxing requires an optimal balance between body weight and reaction speed. Body Mass Index (BMI) is a common measure used to assess body composition. For boxers, maintaining weight within the optimal range is crucial for peak performance. Additionally, reaction speed is a key skill in boxing; the ability to quickly respond to an opponent"™s moves can significantly impact match outcomes.Material and Methods. This cross-sectional study utilized quantitative data analysis. Primary data included body weight, height, and reaction speed from a sample of 12 PPLOP Central Java boxing athletes. Data normality was assessed using the Shapiro-Wilk test, while the linearity test evaluated whether the relationships between variables were linear. Bivariate correlation tests were conducted. The study used Body Mass Index and Hand Touch Reaction tests with validity levels of 0.98 and 0.323, respectively, for measuring body weight, height, and reaction speed.Results. There is a relationship between body weight and reaction speed with a sig value of .003 <0.05 with a negative relationship direction. 2. there is no relationship between height and reaction speed with a sig value of (0.798>0.05) with a negative relationship direction, 3. there is a relationship between body mass index and reaction speed with a sig value of .001 <0.05 with a negative relationship directionConclusion. Based on the results of the study it can be concluded that there is a linear relationship between body weight and reaction speed, there is no linear relationship between height and reaction speed and there is a linear relationship between body mass index and reaction speed.